Control System Design Concept for Coconut Shell Charcoal Powder Processing Equipment as a Base Material for Herbal Toiletries Integrated with PV System - Simanjuntak, Christopel H.; Rumokoy, Stieven Netanel; Warokka, Adriyan; Dodie, Stanley B.; Rambing, Precylia R.; Makalew, Mario Y.; Mansauda, Karlah Lifie Riani (CCIT (Creative Communication and Innovative Technology) Journal, 2026)
Various raw materials with enhanced benefits have been discovered for the toiletries industry. One promising material is coconut shell charcoal powder (Cocos nucifera), which can be used as a base ingredient in herbal toiletries formulations. However, its production process still faces challenges, particularly in terms of technology and operations, especially for small and medium enterprises. Therefore, this study aims to design a control system concept for a coconut shell charcoal powder processing unit integrated with a PV system. The methods used include a literature review and a descriptive study through interviews with practitioners and academics specializing in charcoal powder production systems and herbal toiletries formulation. The result of this study is a conceptual design of a control system equipped with a remote monitoring system to oversee and regulate the coconut shell charcoal powder production process more efficiently.